How Students Learn: History in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: History in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness.
Keywords: Education

How Students Learn: Science in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: Science in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. Organized for utility, the book explores how the principles of learning can be applied in science at three levels: elementary, middle, and high school. Leading educators explain in detail how they developed successful curricula and teaching approaches, presenting strategies that serve as models for curriculum development and classroom instruction. Their recounting of personal teaching experiences lends strength and warmth to this volume. This book discusses how to build straightforward science experiments into true understanding of scientific principles. It also features illustrated suggestions for classroom activities.
Keywords: Education

How Students Learn: Mathematics in the Classroom - National Research Council (The National Academies Press, 2005)
How Students Learn: Mathematics in the Classroom builds on the discoveries detailed in the best-selling How People Learn. Now these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. This book shows how to overcome the difficulties in teaching math to generate real insight and reasoning in math students. It also features illustrated suggestions for classroom activities.
Keywords: Education

Electronic Brains: Stories from the Dawn of the Computer Age - Hally, Mike (The National Academies Press, 2005)
We've come so far, so fast. Within a relatively short period of time, we've managed to put enormous computing power in offices and homes around the globe. But before there was an IBM computer, before there were laptops and personal PCs, there were small independent teams of pioneers working on the development of the very first computer. Scattered around the globe and ranging in temperament and talent, they forged the future in basement labs, backyard, workshops, and old horse barns. Tracing the period just after World War II when the first truly modern computers were developed, Electronic Brains chronicles the escapades of the world's first "techies." Some of the initial projects are quite famous and well known, such as "LEO", the Lyons Electronic Office, which was developed by the catering company J. Lyons & Co. in London in the 1940s. Others are a bit more arcane, such as the ABC, which was built in a basement at Iowa State College and was abandoned to obscurity at the beginning of WWII. And then - like the tale of the Rand 409 which wss constructed in a barn in Connecticut under the watchful eye of a stuffed moose - there are the stories that are virtually unknown. All combine to create a fascinating history of a now-ubiquitous technology. Relying on extensive interviews from surviving members of the original teams of hardware jockeys, author Mike Hally recreates the atmosphere of the early days of computing. Rich with provocative and entertaining descriptions, we are introduced go the many eccentric, obsessive, and fiercely loyal men and women who laid the foundations for the computerized world in which we now live. As the acronyms fly fast and furious - UNIVAC, CSIRAC, and MESM, to name just a few - Electronic Brains provides a vivid sense of time, place, and science.
Keywords: Explore Science; Computers and Information Technology

How Students Learn: History, Mathematics, and Science in the Classroom - National Research Council (The National Academies Press, 2005)
How do you get a fourth-grader excited about history? How do you even begin to persuade high school students that mathematical functions are relevant to their everyday lives? In this volume, practical questions that confront every classroom teacher are addressed using the latest exciting research on cognition, teaching, and learning. How Students Learn: History, Mathematics, and Science in the Classroom builds on the discoveries detailed in the bestselling How People Learn. Now, these findings are presented in a way that teachers can use immediately, to revitalize their work in the classroom for even greater effectiveness. Organized for utility, the book explores how the principles of learning can be applied in teaching history, science, and math topics at three levels: elementary, middle, and high school. Leading educators explain in detail how they developed successful curricula and teaching approaches, presenting strategies that serve as models for curriculum development and classroom instruction. Their recounting of personal teaching experiences lends strength and warmth to this volume. The book explores the importance of balancing students' knowledge of historical fact against their understanding of concepts, such as change and cause, and their skills in assessing historical accounts. It discusses how to build straightforward science experiments into true understanding of scientific principles. And it shows how to overcome the difficulties in teaching math to generate real insight and reasoning in math students. It also features illustrated suggestions for classroom activities. How Students Learn offers a highly useful blend of principle and practice. It will be important not only to teachers, administrators, curriculum designers, and teacher educators, but also to parents and the larger community concerned about children's education.
Keywords: Education

Operational Differences and Similarities Among the Motorcoach, School Bus, and Trucking Industries - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 6: Operational Differences and Similarities Among the Motorcoach, School Bus, and Trucking Industries is designed as a single resource for information on profiles, safety statistics, and general business operations for these three commercial vehicle industries.
Keywords: Transportation and Infrastructure

Smart Growth and Transportation: Issues and Lessons Learned - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Conference Proceedings 32: Smart Growth and Transportation: Issues and Lessons Learned summarizes the highlights of a conference—Providing a Transportation System to Support Smart Growth: Issues, Practice, and Implementation—held September 8-10, 2002, in Baltimore, Maryland. The conference was designed to address how transportation policy makers and frontline professionals can support the diverse goals that different communities associate with smart growth.
Keywords: Transportation and Infrastructure

Principles and Practices for a Federal Statistical Agency: Third Edition - National Research Council (The National Academies Press, 2005)
Since 1992, the Committee on National Statistics (CNSTAT) has produced a book on principles and practices for a federal statistical agency, updating the document every 4 years to provide a current edition to newly appointed cabinet secretaries at the beginning of each presidential administration. This third edition presents and comments on three basic principles that statistical agencies must embody in order to carry out their mission fully:
Keywords: Behavioral and Social Sciences; Computers and Information Technology; Surveys and Statistics

Informing the Future: Critical Issues in Health, Third Edition - Institute of Medicine (The National Academies Press, 2005)
Keywords: Health and Medicine

Mineral Tolerance of Animals: Second Revised Edition, 2005 - National Research Council (The National Academies Press, 2005)
Excess minerals in the diet and water of animals can have an adverse effect on animal health, consumers, and the environment. Preventing unsafe mineral exposure is a fundamental part of animal nutrition and management. At the request of the Food and Drug Administration, the National Academies convened a committee to make recommendations on animal tolerances and toxic dietary levels, updating a 1980 report on mineral tolerance in domestic animals. Based on a review of current scientific data and information, the report sets a "maximum tolerable level" (MTL) for each mineral as it applies to the diets of farm animals, poultry, and fish. The report includes an analysis of the effects of toxic levels in animal diets, and it identifies elements that pose potential human health concerns. The report recommends research that includes a better characterization of animal exposure to minerals through feedstuffs; a better understanding of the relationship between mineral concentrations in feed and water and the levels in consumer products such as meat, milk, and eggs; and more research on the maximum tolerable level of minerals for aquatic and companion animals.
Keywords: Agriculture

Focusing on Learning: Proceedings and Transcripts from Mathematics/Science Partnership Workshops (The National Academies Press, 2005)
The Mathematics/Science Partnerships Program resulted from the federal No Child Left Behind legislation enacted in 2001. Supported through funds administered by the NSF and the U.S. Department of Education, it will unite multiple stakeholders in the K-12, higher education, and business communities to ensure that all students have access to, are prepared for, and are encouraged to participate and succeed in, challenging and advanced mathematics and science courses; enhance the quality, quantity and diversity of the K-12 mathematics and science teacher workforce; and develop evidence-based outcomes that contribute to our understanding of how students effectively learn mathematics and science.
Keywords: Education

Focusing on Assessment of Learning: Proceedings and Transcripts from Mathematics/Science Partnership Workshops (The National Academies Press, 2005)
The Mathematics/Science Partnerships Program resulted from the federal No Child Left Behind legislation enacted in 2001. Supported through funds administered by the NSF and the U.S. Department of Education, it will unite multiple stakeholders in the K-12, higher education, and business communities to ensure that all students have access to, are prepared for, and are encouraged to participate and succeed in, challenging and advanced mathematics and science courses; enhance the quality, quantity and diversity of the K-12 mathematics and science teacher workforce; and develop evidence-based outcomes that contribute to our understanding of how students effectively learn mathematics and science.
Keywords: Education

Progress in Preventing Childhood Obesity: Focus on Schools: Brief Summary: Institute of Medicine Regional Symposium - Institute of Medicine (The National Academies Press, 2005)
Obesity is now an epidemic among children and adolescents in the United States. Nationwide, roughly nine million children over six years of age are obese—with elevated risks of both health conditions, such as diabetes and hypertension, and poor quality of life, possibly throughout adulthood. The Institute of Medicine (IOM) report, Preventing Childhood Obesity: Health in the Balance, was released in September 2004 and identified promising approaches for obesity prevention efforts and a set of recommendations for a variety of stake holders and sectors.
Keywords: Health and Medicine

Lessons Learned Between Hurricanes: From Hugo to Charley, Frances, Ivan, and Jeanne: Summary of the March 8, 2005 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2005)
Keywords: Earth Sciences

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 5, Vanpools and Buspools - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Traveler Response to Transportation System Changes, Chapter 5 -- Vanpools and Buspools examines the effects of travel times, pricing, and other consequences from the decision to vanpool. The report also quantifies vanpooling and buspooling as best can be done; looks at vanpooling trends; examines rider survey information; identifies indicators of market potential; and explores cost implications, among other subjects.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 13, Parking Pricing and Fees - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 13 -- Parking Pricing and Fees examines traveler response to both the introduction of parking pricing and fees and to changes in the level, structure, or method of application of parking fees. Included are actions that can change the costs to users of parking even without fee changes, notably through elimination of employer parking subsidies and by fee structures that differentiate by modes of parking (short/long term) or travel (drive-alone/ridesharing).The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Memory: The Key to Consciousness - Thompson, Richard F.; Madigan, Stephen A. (The National Academies Press, 2005)
Memory is perhaps the most extraordinary phenomenon in the natural world. Every person’s brain holds literally millions of bits of information in long-term storage. This vast memory store includes our extensive vocabulary and knowledge of language; the tremendous and unique variety of facts we’ve amassed; all the skills we’ve learned, from walking and talking to musical and athletic performance; many of the emotions we feel; and the continuous sensations, feelings, and understandings of the world we term “consciousness.” And we routinely access this tremendous volume of data in the blink of an eye. Without memory there can be no mind as we understand it.
Keywords: Biology and Life Sciences

The Language of Life: How Cells Communicate in Health and Disease - Niehoff, Debra (The National Academies Press, 2005)
Cooperation requires conversation. Human beings speak to one another. Sounds, scents, and postures allow animals to make their point. While individual cells can’t talk, hiss, growl, or bare their teeth, they nevertheless communicate regularly. Their language is based not on words or gestures, but on chemistry —using molecules where we would use words, constructing sentences from chains of proteins. The cells that make up the bodies of muticellular organisms inform, wheedle, command, exhort, reassure, nurture, criticize, and instruct each other to direct every physiological function, report every newsworthy event, record every memory, heal every wound. And each of those chemical conversations represents an opportunity for scientists and physicians.
Keywords: Biology and Life Sciences; Health and Medicine

Public Financing and Delivery of HIV/AIDS Care: Securing the Legacy of Ryan White - Institute of Medicine (The National Academies Press, 2005)
Each year it is estimated that approximately 40,000 people in the U.S. are newly infected with HIV. In the late 1990s, the number of deaths from AIDS dropped 43% as a result of highly active antiretroviral therapy. Unfortunately, the complex system currently in place for financing and delivering publicly financed HIV care undermines the significant advances that have been made in the development of new technologies to treat it. Many HIV patients experience delays in access to other services that would support adhering to treatment. As a result, each year opportunities are missed that could reduce the mortality, morbidity, and disability suffered by individuals with HIV infections. Public Financing and Delivery of HIV/AIDS Care examines the current standard of care for HIV patients and assesses the extent the system currently used for financing and delivering care allows individuals with HIV to actually receive it. The book recommends an expanded federal program for the treatment of individuals with HIV, administered at the state level. This program would provide timely access and consistent benefits with a strong focus on comprehensive and continuous care and access to antiretroviral therapy. It could help improve the quality of life of HIV/AIDS patients, as well as reduce the number of deaths among those infected.
Keywords: Health and Medicine

Knowledge-Action Systems for Seasonal to Interannual Climate Forecasting: Summary of a Workshop - National Research Council (The National Academies Press, 2005)
The National Academies' Roundtable on Science and Technology for Sustainability hosted a workshop "Knowledge-Action Systems for Seasonal to Interannual Climate Forecasting" in 2004 to discover and distill general lessons about the design of effective systems for linking knowledge with action from the last decade's experience with the production and application of seasonal to interannual climate forecasts. Workshop participants described lessons they had learned based on their experiences developing, applying, and using decision support systems in the United States, Columbia, Brazil, and Australia. Some of the key lessons discussed, as characterized by David Cash and James Buizer, were that effective knowledge-action systems: define and frame the problem to be addressed via collaboration between knowledge users and knowledge producers; tend to be end-to-end systems that link user needs to basic scientific findings and observations; are often anchored in "boundary organizations" that act as intermediaries between nodes in the system - most notably between scientists and decision makers; feature flexible processes and institutions to be responsive to what is learned; use funding strategies tailored to the dual public/private character of such systems; and require people who can work across disciplines, issue areas, and the knowledge–action interface.
Keywords: Earth Sciences